Impact of a Virtual Reading Intervention in Children with Dyslexia: Is Efficacy Different Compared to Face-to-Face Interventions? (Revista de Psicología, 2023)
As a result of the COVID-19 pandemic situation, the psychoeducational work was forced to carry out virtual interventions. In this work, progress in reading skills was compared in face-to-face vs. virtual intervention in patients with dyslexia. The evolution of 26 patients from 1st to 3rd grade exposed in both formats to the same reading intervention with a cognitive program, was analyzed. The results showed that both in the virtual and face-to-face modalities, an improvement was achieved in phonological skills, reading fluency and decoding, with no significant difference across modalities. In conclusion, virtual interventions can be effective if an explicit and systematic treatment is carried out, with an evidencebased program and based on an initial faceto-face bond.
Keywords: pandemic situation; reading skills; reading strategies; phonological skills; reading fluency; psychopedagogical intervention.